2007
DOI: 10.1016/j.str.2007.06.015
|View full text |Cite
|
Sign up to set email alerts
|

An IgG-like Domain in the Minor Pilin GBS52 of Streptococcus agalactiae Mediates Lung Epithelial Cell Adhesion

Abstract: Streptococcus agalactiae is the leading cause of neonatal pneumonia, sepsis, and meningitis. The pathogen assembles heterotrimeric pilus structures on its surface; however, their function in pathogenesis is poorly understood. We report here the crystal structure of the pilin GBS52, which reveals two IgG-like fold domains, N1 and N2. Each domain is comprised of seven antiparallel beta strands, an arrangement similar to the fold observed in the Staphylococcus aureus adhesin Cna. Consistent with its role as an ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
120
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 106 publications
(127 citation statements)
references
References 46 publications
4
120
1
Order By: Relevance
“…The closest structural homologues of the N-and C-domains of SpaA are the 2 CnaB-type domains of the Streptococcus agalactiae minor pilin GBS52 (15). In particular, the SpaA C-domain has significant sequence identity (25%) and structural similarity (rmsd 1.7 Å over 91 equivalent C␣ atoms) with the N2 domain of GBS52.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The closest structural homologues of the N-and C-domains of SpaA are the 2 CnaB-type domains of the Streptococcus agalactiae minor pilin GBS52 (15). In particular, the SpaA C-domain has significant sequence identity (25%) and structural similarity (rmsd 1.7 Å over 91 equivalent C␣ atoms) with the N2 domain of GBS52.…”
Section: Resultsmentioning
confidence: 99%
“…GBS52, a minor pilin from S. agalactiae that seems to correspond functionally to SpaB, comprises 2 CnaB-type domains (15), and its C-terminal N2 domain closely resembles the SpaA C-domain, including the internal isopeptide bond. Sequence comparisons show that the S. pyogenes minor pilin Cpa also has a C-terminal domain homologous with the C-domain of the S. pyogenes major pilin Spy0128, again including an internal isopeptide bond (5).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Further investigations have shown that similar isopeptide bonds can be found as internal cross-links in other proteins. Examination of previously determined structures of a minor pilin GBS52 from Streptococcus agalactiae (13) and the CnaA and CnaB domains of a collagen-binding adhesin from Staphylococcus aureus (14 -16) revealed constellations of Lys-AsnGlu/Asp residues similar to those that form the internal crosslinks in Spy0128, and examination of the electron density confirmed their probable presence in those cases where the x-ray data were available (3). Sequence comparisons showed that similar domains, with corresponding Lys-Asn-Glu/Asp residues, are present in many cell surface proteins of Grampositive bacteria.…”
mentioning
confidence: 94%
“…By solving the crystallographic structure of BP2a (from GBS strain 515), Nuccitelli et al (3) discern four Ig-like domains (D1-D2-D3-D4), which could be anticipated to function as independent folding units (17,18). Individual domains are tested as subunit vaccines; however, only D3 elicits protection similar to full-length BP2a (3).…”
mentioning
confidence: 99%